2011
DOI: 10.1681/asn.2010060582
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aspirin Associates with Longer Primary Patency of Hemodialysis Grafts

Abstract: Extended-release dipyridamole plus low-dose aspirin (ERDP/ASA) prolongs primary unassisted graft patency of newly created hemodialysis arteriovenous grafts, but the individual contributions of each component are unknown. Here, we analyzed whether use of aspirin at baseline associated with primary unassisted graft patency among participants in a randomized trial that compared ERDP/ASA and placebo in newly created grafts. We used Cox proportional hazards regression, adjusting for prespecified baseline comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
6
22
0
Order By: Relevance
“…Treatment with dipyridamole plus aspirin has a significant but modest effect in reducing the risk of stenosis and improving the duration of primary unassisted patency of newly created grafts [76] . Dixon et al [77] support that use of aspirin is associated with a trend toward longer primary unassisted patency of newly placed HD grafts, similar to that observed for extended-release dipyridamole plus lowdose aspirin (ERDP/ASA). Daily fish oil ingestion did not decrease the proportion of grafts with loss of native patency within 12 mo, although fish oil improved some relevant secondary outcomes, such as graft patency, rates of thrombosis and interventions [78] .…”
Section: Permanent Vamentioning
confidence: 67%
“…Treatment with dipyridamole plus aspirin has a significant but modest effect in reducing the risk of stenosis and improving the duration of primary unassisted patency of newly created grafts [76] . Dixon et al [77] support that use of aspirin is associated with a trend toward longer primary unassisted patency of newly placed HD grafts, similar to that observed for extended-release dipyridamole plus lowdose aspirin (ERDP/ASA). Daily fish oil ingestion did not decrease the proportion of grafts with loss of native patency within 12 mo, although fish oil improved some relevant secondary outcomes, such as graft patency, rates of thrombosis and interventions [78] .…”
Section: Permanent Vamentioning
confidence: 67%
“…These patients with hypercoagulable states or combined thrombophilia should be preoperatively identified to tailor antithrombotic therapy and intensify surveillance, especially during the first, most vulnerable months after surgery. However, the optimal prophylaxis for access thrombosis and stenosis is not settled despite extensive efforts (29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…9 Subsequent analysis suggested that aspirin alone might be as effective as dipyridamole plus aspirin. 10 In the study by Lok et al, more than half of all patients were taking aspirin, and more than 10% were taking clopidogrel at baseline. This suggests that fish oil may even be effective in a population of patients receiving aspirin or other antiplatelet agents.…”
Section: Does Time Matter?mentioning
confidence: 99%